The Impact of Ethical Leadership on Corporate Performance - Pratiwi, Henny; Wafi, Muhammad Fadlil; Riyadh, Muhammad Ilham; Sina, Ibnu; Pane, Elvy Carolina; Yusuf, Husainah (Universitas Teuku Umar, 2024)
Ethical leadership encourages positive employee behavior and enhances organizational performance by emphasizing ethical dimensions in management. The key elements of ethical leadership include honesty, integrity, trust, and fairness. Ethical leaders integrate moral principles into their values, beliefs, and actions while respecting the rights and dignity of others. This study aims to analyze the ethical leadership factors that influence corporate performance. Multiple regression analysis is used to evaluate the relationship between ethical leadership and employee performance at PT. Perkebunan Nusantara II (Persero) Regional I. The Saturation Sampling method is applied to determine the sample. The tests conducted include classical assumption tests, hypothesis tests, and data quality tests. The study results indicate that the telling and selling leadership styles do not significantly affect employee performance. Conversely, participative and delegative leadership styles have a positive impact. The simultaneous significance test shows that independent variables collectively influence the dependent variable, with the F-calculated value exceeding the F-table value and a significance probability below 0.05. This indicates that ethical leadership involving participation and delegation is more effective in improving employee performance.